Between chaos and the cosmos: the imaginary of traditional climbing. Issue 4 (2nd October 2022) - Ito, Eric Sioji; Saura, Soraia Chung; Zimmermann, Ana Cristina
ABSTRACT: The imaginary is constituted as one of the bases of human desires. The images created in us when in contact with the environment sometimes drive or hinder human actions. A study on the climbers' imaginary can help in understanding the impulses that move them to this activity. Thus, the objective of this article is to develop a reflection on the imaginary of traditional climbing, seeking images that inspire climbers in their relationship with the world. The analyses were elaborated through the following research process: search in historiography and mythology about representations that reveals the climber's imaginary through time; dialogue with authors of imaginary studies and research on climbing and adventure sports; ethnographic field research with interviews conducted at famous climbing points of the Chilean and Argentine Patagonia. The image of the traditional climber is configured beyond the ascending movements in the cliffs. It has a dynamic structure guided intimately in the relationship of the body with the mountain environment. To clarify these reflections, we coined the expression "intimate body", in line with the thoughts of Yi-Fu Tuan, Merleau-Ponty, and Ian Heywood. Such elaborations highlight the importance of the body-environment relationship in the human imagination and its influence on human impulses.